cGAMP the travelling messenger - Blest, Henry T. W.; Chauveau, Lise (Frontiers in Immunology, 2023)
2’3’-cGAMP is a key molecule in the cGAS-STING pathway. This cyclic dinucleotide is produced by the cytosolic DNA sensor cGAS in response to the presence of aberrant dsDNA in the cytoplasm which is associated with microbial invasion or cellular damage. 2’3’-cGAMP acts as a second messenger and activates STING, the central hub of DNA sensing, to induce type-I interferons and pro-inflammatory cytokines necessary for responses against infection, cancer or cellular stress. Classically, detection of pathogens or danger by pattern recognition receptors (PRR) was thought to signal and induce the production of interferon and pro-inflammatory cytokines in the cell where sensing occurred. These interferon and cytokines then signal in both an autocrine and paracrine manner to induce responses in neighbouring cells. Deviating from this dogma, recent studies have identified multiple mechanisms by which 2’3’-cGAMP can travel to neighbouring cells where it activates STING independent of DNA sensing by cGAS. This observation is of great importance, as the cGAS-STING pathway is involved in immune responses against microbial invaders and cancer while its dysregulation drives the pathology of a wide range of inflammatory diseases to which antagonists have been elusive. In this review, we describe the fast-paced discoveries of the mechanisms by which 2’3’-cGAMP can be transported. We further highlight the diseases where they are important and detail how this change in perspective can be applied to vaccine design, cancer immunotherapies and treatment of cGAS-STING associated disease.